E-Readiness of Integrated Information Systems Using STOPE Framework in Udayana University - Syahputri, Theca Difa Yulian; Githa, Dwi Putra; Pratama, I Putu Agus Eka (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi); Vol. 9, No. 1, April 2021DO - 10.24843/JIM.2021.v09.i01.p02, 2021)
Many industries and institutions have switched to digital technology, an integrated information technology system, since we entered the era of the industrial revolution 4.0. In implementing new strategies, problems often occur because they do not assess technology readiness (e-readiness) to be built. Therefore, it is necessary to conduct a technology readiness assessment (e-readiness) either before or after the new system is implemented to assess how ready it is. The review can use the STOPE framework to be flexible so that this framework can be adjusted to the case study handled. IMISSU is an integrated management information system technology belonging to Udayana University. The results of the IMISSU e-readiness assessment found that the readiness of Udayana University in implementing IMISSU is at a very ready level (4 of 4). Assessment using the STOPE framework includes three levels, namely the domain, sub-domain, and sub-sub-domain levels. The study was conducted by distributing 100 questionnaires divided among various academicians in the university, adjusted to the STOPE framework domain.